O egoísmo e os artifícios humanos na teoria das origens da justiça no Tratado da natureza humana: teria sido Hume um hobbesiano? - Julio Andrade Paulo (2018)
The aim of this paper is to analyze if Hume, in the Treatise of Human Nature, effectively resorted to a conception of human nature of the egoistic, individualistic and interested type in order to formulate his theory of the origins of justice, if he was aware of it and if he can be considered a Hobbesian on account of this. Hume, in classifying justice as an artificial virtue, wanted to draw attention to the novelty and originality of his thought. In such an undertaking, he says that the instinctive principles of sexual passion and affection to the offspring are important but do not prevent the outcropping of the egoism present in the human being and also says that this feeling is only remedied by means of an artifice that occurs in the context of the human conventions: a self-restraint to better satisfy itself. For us, such an artifice remarkably mirrors Hobbes's theory of the rational artifice of the renunciation of unrestricted freedom for the sake of life in society, effected by means of a social pact. We argue that Hume, in the Treatise, did not imagine that he had entered into this philosophical approximation to Hobbes, for he considered that he sufficiently had refuted certain doctrines associated with the English philosopher concerning the ideas of state of nature, social pact, promises, government, and resistance; in the Second Enquiry, his open criticisms of Hobbes and the selfish systems of moral philosophy, as well as his change of tone in his discussions concerning justice, indicate that he himself concluded that in his work of youth he was more Hobbesian than he wished to have been, so much that he tried to reverse this scenario. We understand that although the mature Hume has acknowledged his approximation to Hobbes with respect to the theory of the origins of justice presented in the Treatise, it is not possible to consider the Scottish philosopher as a Hobbesian proper, because he never wanted to be as such and because his perspective of approaching the subject is diverse